IOTA simple rules for discriminating between benign and malignant adnexal masses: prospective external validation. (2nd September 2013) - Alcázar, J. L.; Pascual, M. Á.; Olartecoechea, B.; Graupera, B.; Aubá, M.; Ajossa, S.; Hereter, L.; Julve, R.; Gastón, B.; Peddes, C.; Sedda, F.; Piras, A.; et al.
ABSTRACT Objective To determine the diagnostic performance of International Ovarian Tumor Analysis (IOTA) 'simple' rules for discriminating between benign and malignant adnexal masses. Methods A prospective study was performed between January 2011 and June 2012. Eligible patients were women diagnosed with a persistent adnexal mass who presented to the participating centers. Four trainees evaluated the adnexal mass by transvaginal ultrasound under the supervision of an expert examiner. The trainee analyzed the mass according to IOTA simple rules and provided a diagnosis of benign, malignant or inconclusive. All women included in the study underwent surgery and tumor removal in the center of recruitment. Diagnostic performance was assessed by calculating sensitivity, specificity and positive (LR+) and negative (LR–) likelihood ratios. Results A total of 340 women were included (mean patient age, 42.1 (range, 13–79) years). Of the tumors, 55 (16.2%) were malignant and 285 (83.8%) were benign. The IOTA simple rules could be applied in 270 (79.4%) cases. In these cases, sensitivity was 87.9% (95% CI, 72.4–95.2), specificity 97.5% (95% CI, 94.6–98.8), LR+ 34.7 (95% CI, 15.6–77.3) and LR– 0.12 (95% CI, 0.05–0.31). Conclusions Application of the IOTA simple rules yielded acceptable results in terms of specificity in the hands of non‐expert examiners. However, with non‐expert examiners there was a 12% false‐negative rate, which is relatively high. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.